Assessing the knowledge of dietitians regarding diet and oral health in Bengaluru city - Padma Keshav Bhat; Shwetha Hulikere Lingaraj; C N Aruna (Journal of Indian Association of Public Health Dentistry, 2014)
Objective: To assess the knowledge of dietitians regarding diet and oral health in Bengaluru city. Materials and Methods: A cross-sectional study was conducted among the life members of Indian Dietetic Association, Bangalore chapter. A close ended, self-administered 23 item questionnaire was distributed and collected after 10 min. The data was subjected to statistical analysis. Results: About 36% felt dietary supplements can prevent oral mucosal diseases, and only 12% were aware that high content of fluoride in water leads to abnormal tooth defects. Overall knowledge of dietitians pertaining diet and oral health was 56.48%. Conclusion: Study highlights the deficiency of knowledge of dietitians regarding oral health. The multifaceted interactions between diet and oral health in practice, education and research in both dietetics and dentistry merit detailed delineation.